A novel RFID and capacitive sensing based smart bookshelf - Liu, Wei (2013)
Radio frequency identification (RFID) has become more popular and used ubiquitously in various applications nowadays. They are also commonly found in close proximity to human body in everyday life. There has been growing concerns over health issues caused by the widely spread radio technologies which might be hazardous if operated in close proximity of human beings continuously. However, in our novel approach we have utilized the capacitive sensing instead of radio waves for human proximity detection hence, eliminating any hazard associated with the radio frequencies. Moreover, switching off RF transmission when it is not required will not only reduce the amount of radiation, but it would also save energy. Proximity detection through the use of capacitive sensing instead of RF radiation can also be a strategic, economic, energy efficient and value-adding feature to implement into many possible applications, including RFIDs.